INNOVATIVE PEDAGOGY AND ITS REGULATORY AND LEGAL FOUNDATIONS IN THE MODERN EDUCATIONAL PROCESS - Ktaybekova Zulfiya Kengesbaevna; Abdullaeva Uguldjan Ibadullaevna; Irgashova Maripat Abdinazarovna; Irada Ikramshikovna Rejametova; Rakhimova Saida Durdiyevna (The Bioscan, 2025)
This article explores the crucial role of innovative pedagogy in the modern educational process. The rapid development of science and technology necessitates the integration of new approaches, methods, and technologies into teaching and learning practices. Special attention is given to the regulatory and legal frameworks that support the modernization of education systems, enhance students’ creativity, and foster independent thinking.